To study the role of tofacitinib and betamethasone pulse in the treatment of vitiligo at a tertiary care centre: an observational comparative study - Rashmi Singh; Surabhi Shandilya; Kamalpreet Kaur Bhaikhel; Gopi Krishna Maddali (Pigment International)
Background: According to recent updates, both genetic and non-genetic factors play a role in the pathogenesis of vitiligo, and CD8T lymphocytes and interferon γ are also known to result in vitiligo. The new oral biologic tofacitinib, which is a Janus kinase inhibitor, is a new addition to the armamentarium of immunosuppressive therapy to halt disease progression in vitiligo. Tofacitinib is also known to inhibit IFN-γ mediated inflammation, which is an important step in the development of vitiligo lesions. Aims and objectives: The aim of this study was to compare tofacitinib with betamethasone pulse in reducing the disease activity with respect to reduction in VASI (vitiligo area severity index) and BSA (body surface area) in patients with vitiligo. The primary objective was to see the efficacy of tofacitinib over betamethasone in the treatment of vitiligo, and the secondary objective was to assess its safety in treating vitiligo patients. Methodology: All the patients with vitiligo of age >12 years attending the dermatology clinic of our institute and willing to give written informed consent were included in the study. Group A patients were prescribed betamethasone 4 mg twice weekly, and group B patients were given tofacitinib 5 mg twice daily, followed by sun exposure in both groups, and photography was done at each monthly visit. Results: The mean change in VASI and BSA in the tofacitinib group was better at each visit than in the betamethasone group. The mean VASI scores at baseline, 1st, 2nd, and 3rd visits were 13.64, 12.79, 11.57, and 10.57, respectively, and the mean BSA at baseline, 1st, 2nd, and 3rd visits were 10.80, 9.75, 8.30, and 7.75 respectively, in the betamethasone group. Similarly, in the tofacitinib group, mean BSA values from baseline to the 3rd visit were consecutively 11.47, 9.50, 7.50, and 5.25, and mean VASIs were 14.92, 12.46, 9.46, and 7.08, respectively. Further, mean changes in BSA and VASI from baseline at each visit. as depicted in graphs 1 and 2, were more in tofacitinib group. There was no side effect in either group at any of the visits. Conclusion: Tofacitinib, along with sun exposure, can cause faster repigmentation and faster control of disease activity, as evident from mean changes at each visit, than oral betamethasone pulse in vitiligo patients.